RESEARCH ON REDUCING THE PILE OF YARN ON A RING-SPINNING MACHINE - Abdumutaliev Inomjon Muhammadjon ogli; Bobojanov Husankhon Tohirovich; Yusupov Alijon Abdujabbor ogli; Aripova Shakhlo Raufovna (European Science Publishing, 2024)
Yarn piling on ring spinning machines is a persistent issue affecting the quality of yarn and the efficiency of textile production. This study investigates methods to reduce yarn piling by optimizing spinning parameters, including spindle speed, twist multiplier, and fibre properties. Experimental trials were conducted using varying conditions to assess their impact on pile formation and yarn quality. The results indicate that reducing spindle speed and adjusting the twist multiplier significantly decreased yarn piling while maintaining tensile strength. These findings offer practical guidelines for manufacturers to enhance productivity and product quality, reducing operational costs and waste in textile production.
Keywords: Ring spinning machine, yarn piling, textile production, twist multiplier, spindle speed, fibre properties, yarn quality improvement, textile manufacturing efficiency.